THE USE OF POP SONG WITH LYRICS TO TEACH PRESENT FUTURE TENSE - Fitriani, Julfanida; Fitriani, Fitriani; Sudarsono, Sudarsono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research was to investigate the effectiveness of using pop song with lyrics as a medium to teach present future tense to Year-10 students of SMA Negeri 09 Pontianak in Academic Year 2017/2018. It was a pre-experimental study with a single group pre-test post-test design. The sample was Learning Group X MIA 3 of Year-10 that consisted of 36 students. The technique and the tools of data collection of this research was a measurement technique by giving the students a written test in a multiple choice form which consisted of 20 items. The research findings showed that the students’ mean score of pre-test was 43.19 and the students’ mean score of post-test was 83.61 It means that the score after the treatment was higher than before the treatment. The treatment affected the teaching of present future tense significantly where the t-value is 23.36 and the degree of the effectiveness of the treatment is 3.73. Key Words: Pop Song with Lyrics, Present Future Tense.